The feasibility of surgical salvage of thrombosed arteriovenous fistula by an interventional nephrologist - Seong Cho (The Korean Society of Nephrology, 2017)
Background: Salvage of a thrombosed arteriovenous fistula (AVF) by secondary fistula conversion may be more effective than a conventional endovascular procedure for forearm fistula thrombosis. Surgical access procedures are an undeveloped area in interventional nephrology compared to endovascular procedures. Herein, the author report the results of surgical salvage of thrombosed AVFs by interventional nephrologists. Methods: The author retrospectively analyzed 52 surgical salvage procedures for AVF thrombosis (radiocephalic fistula = 44 cases, brachiocephalic fistula = 8 cases) that were performed by interventional nephrologist between March 2007 and January 2016. Results: Secondary fistula formation using the proximal vein was performed for 46 cases (88.5%); outflow rerouting was performed for two cephalic-arch stenosis cases (3.9%), simple thrombectomy was performed for two cases (3.9%), and a graft interposition was performed for two cases (3.9%). Technical success after the surgical procedures was achieved in 51 cases (98.1%), and 39 AVFs (75.0%) were prepared for immediate puncturing without catheter insertion. The primary and secondary patency rates for AVF at 6, 12, 18, and 24 months were 88.5%, 83.2%, 83.2%, and 83.2% and 96.0%, 96.0%, 93.2%, and 93.2%, respectively. The re-intervention rate was 0.27 ± 0.92/patient/ year. Conclusion: Based on these results, the author conclude that surgical salvage of a thrombosed AVF, when performed under local anesthesia by a skilled interventional nephrologist, offers favorable short- and long-term success and should be the preferred treatment.